Corporate governance and future skills development through lifelong learning - Ilyasova Assem (Theoretical Hypotheses and Empirical Results, 2025)
Modern organizations strive for sustainable development and competitiveness, which requires effective corporate governance and investments in human capital. One of the key tools for this is continuing education programs that promote the development of future skills. In the context of digital transformation and rapid changes in the labor market, employees must have critical thinking, creativity, digital literacy, adaptability, and the ability to self-learn. Corporate governance plays an important role in creating conditions for professional growth by introducing educational initiatives focused on relevant competencies. Continuous training helps to improve the skills of employees, improve teamwork, productivity and the innovative potential of the company. In addition, such programs help to reduce staff turnover and increase staff motivation. The article discusses corporate governance strategies aimed at developing future skills, as well as the benefits of continuing education for employees and organizations.